An Organizational Perspective on Patenting and Open Innovation - Bhaskarabhatla, Ajay; Hegde, Deepak (Organization Science, 2014)
Achange in U.S. patent law in the early 1980s increased the value of patents, particularly for firms in the electronics and semiconductors industry, yet many of the industry’s leading firms did not embrace patenting after the change. We show through an in-depth study of International Business Machines (IBM), the world’s largest patentee, that the company’s practices during much of the 1980s discouraged patenting. IBM adopted pro-patent management practices in 1989 after the installation of a new research and development head and in the face of faltering financial performance. IBM’s increased patenting and licensing activities improved its financial bottom lines but curtailed its industry-wide knowledge spillovers. These causes and consequences of pro-patent practices are visible in several other large U.S. corporations. Thus, in the context of the “patent explosion” of the 1980s, we show that intraorganizational forces such as inertia, financial pressures, and new leadership shaped established firms’ uptake of pro-patent management practices and their success. Our findings also suggest that pro-patent practices associated with “open innovation” may stem the free flow of knowledge across organizational boundaries.